Social class and democratic leadership : essays in honor of E. Digby Baltzell - Baltzell, E. Digby (Edward Digby), 1915-1996; Bershady, Harold J. (University of Pennsylvania Press, 1989)
Inspired by E. Digby Baltzell's extensive contributions to the field, this collection of essays addresses changing definitions of class, education for leadership, local tyrannies, the extent to which elites have risen into leadership positions, conditions of upper class maintenance, the contributions of the nation's cities to its democratic culture, the shape of democratic leadership, the role of political parties in fulfilling principles of equality and achievement, and the social (not merely political) meaning of democracy.